Teachers competency elements of special education integrated program for national type schools in Johor, Malaysia on Implementation of Individual Education Plan - Mosbiran, Nor Fauziyana; Mustafa, Mohamad Zaid; Ahad, Rosnee; Nordin, Mohd Norazmi (2021)
Teacher competence has always been cited as an important aspect in the implementation of policies set by the government. In the field of special education, teacher competence is a requirement in the development of special needs students (SNS). One of the key things that requires teachers to be competent is to implement an individual education plan (IEP). This study aims to explore the key elements that need to be addressed in the area of teacher competence to achieve effective IEP implementation aspirations for SNS. This study fully utilizes a qualitative approach with interviews as a means of collecting data. Interviews were conducted with 11 respondents comprising teachers of the Special Education Integration Program (SEIP) for national type schools (NTS) in the state of Johor. The selected respondents represented each district within the state of Johor, Malaysia. Interview transcripts generated from the interview sessions, then undergo a thematic analysis process for the purpose of acquiring related elements. The findings show that there are four key elements for the construct of teachers' competencies in the implementation of IEP, namely, knowledge, skills, experience and qualification. The results of this study can be referenced by SEIP teachers for NTS in Johor to produce effective IEPs for SNS.